Ablation of Basic Leucine Zipper Transcription Factor ATF-Like Potentiates Estradiol to Induce Atopic Dermatitis. (16th September 2022) - Zhang, Peng; Liu, Luhao; Lai, Xingqiang; Chen, Rongxin; Guo, Yuhe; JunjieMa,; Chen, Wenhao; Chen, Zheng
Abstract : Background . Atopic dermatitis (AD) is an inflammatory and immune skin disorder. Basic leucine zipper transcription factor ATF-like (BATF) plays a key role in regulating the differentiation and functions of lymphocytes. However, the mechanism underlying the transcriptional regulation of BATF on AD is still not well understood. Methods . BATF knockout (BATF –/– ) and C57BL/6(B6) mice were used for the development of spontaneous dermatitis. 17 β -Estradiol was injected intraperitoneally to induce AD. The lesioned tail skin of the mice was stained with hematoxylin and eosin to analyze the pathological characteristics. Impaired skin barrier function was assessed by measuring the transepidermal water loss (TEWL). The skin epithelial barrier indicators and cytokine mRNA levels were quantified by real-time quantitative PCR. The total serum immunoglobulin E (IgE) levels were measured by enzyme-linked immunosorbent assay (ELISA). T lymphocytes were analyzed using flow cytometry. Results . Ablation of BATF led to the spontaneous development of AD only in female mice and not in male mice. BATF deletion led to elevated serum levels of IgE and increased infiltration of eosinophils, neutrophils, and lymphocytes and promoted cytokine production including IL-4, IL-22, IL-1 β, IFN- γ, and TNF- α in the lesioned tail skin of the mice. The mRNA expression levels of filaggrin and loricrin significantly decreased, while S100A8 and S100A9 increased in female BATF –/– mice. BATF-deficient female mice were found to increase proliferation and IL-5 production by skin-infiltrating CD4 + T cells which implies Th2 activation. Moreover, AD was successfully induced only in the estradiol-treated BATF-deficient male mice and not in WT male mice. Estradiol enhanced the allergic and immunological responses to dermatitis primarily by triggering Th2-type immune responses via enhanced serum IgE and inflammatory cytokine levels in the male BATF –/– mice. Conclusion . The study concluded that BATF potentiates estradiol to induce mouse atopic dermatitis via potentiating inflammatory cytokine releases and Th2-type immune responses and may have important clinical implications for patients with AD.